Enhancement of oil recovery using zirconium-chitosan hybrid composite by adsorptive method. (10th July 2016) - Elanchezhiyan, S. SD.; Sivasurian, N.; Meenakshi, Sankaran
Highlights: We investigated a new sorbent for oil sorption. The Zr-CS-HC exhibit higher oil sorption capacity at pH 3. Oil adsorption on the sorbent was confirmed by FTIR, XRD and SEM with EDAX. Metal chelation enhances the oil sorption. Abstract: Recovery of oil from oil-in-water emulsion has been investigated by many scientists and it continues to be a challenging task for environmental scientists so far. Among all the techniques, adsorption is found to be an appropriate process for the removal of oil from oil-in-water emulsion owing to its high efficiency and easy operation. A hybrid material, zirconium-chitosan composite (Zr-CS-HC) was prepared to remove the oil from oil-in-water emulsion and oil was measured by extractive gravimetric method. Various parameters viz., agitation time, pH, sorbent dosage and initial oil concentration for maximum sorption were optimized. In this study, the maximum oil removal percentage was found to be at pH 3.0 and a minimum contact time of 50 min using prepared sorbent. The pH of the sorption studies revealed that oil sorption was favored in acidic condition. The sorbent was characterized using FTIR, SEM with EDAX, XRD, TGA and DSC; contact angle and heat of combustion. The experimental data were explained using Freundlich, Langmuir, D–R and Tempkin isotherms to find the best fit for the sorption process. Thermodynamic parameters such as Δ G °, Δ H ° and Δ S ° were calculated to understand the nature of sorption process. This work provides a potential platform for the expansion of oil removal technology.